Features for Predicting Absorbable Pulmonary Solid Nodules as Depicted on Thin-Section Computed Tomography - Lin RY; Lv FJ; Fu BJ; Li WJ; Liang ZR; Chu ZG (Dove Medical Press, 2021)
Rui-Yu Lin,* Fa-Jin Lv,* Bin-Jie Fu, Wang-Jia Li, Zhang-Rui Liang, Zhi-Gang Chu Department of Radiology, The First Affiliated Hospital of Chongqing Medical University, Chongqing, People's Republic of China*These authors contributed equally to this workCorrespondence: Zhi-Gang ChuDepartment of Radiology, The First Affiliated Hospital of Chongqing Medical University, 1# Youyi Road, Yuanjiagang, Yuzhong District, Chongqing, 400016, People's Republic of ChinaTel +86 18723032809Fax +86 23 68811487Email chuzg0815@163.comPurpose: To investigate the clinical and computed tomography (CT) characteristics of absorbable pulmonary solid nodules (PSNs) and to clarify CT features for distinguishing absorbable PSNs from malignant ones.Materials and Methods: From January 2015 to February 2021, a total of 316 patients with 348 PSNs (171 absorbable and 177 size-matched malignant) were retrospectively enrolled. Their clinical and CT data were analyzed and compared to determine CT features for predicting absorbable PSNs.Results: Between absorbable and malignant PSNs, there were significant differences in patients' age, lesions' locations, shapes, homogeneity, borders, distance from the pleura, vacuoles, air bronchograms, lobulation, spiculation, halo sign, multiple concomitant nodules and pleural indentation (each P < 0.05). Multivariate analysis revealed that the independent predictors of absorbable PSNs were the following: patient age ≤ 55 years (OR, 2.660; 95% CI, 1.432- 4.942; P = 0.002), homogeneous density (OR, 2.487; 95% CI, 1.107- 5.590; P = 0.027), ill-defined border (OR, 5.445; 95% CI, 1.661- 17.846; P = 0.005), halo sign (OR, 3.135; 95% CI, 1.154- 8.513; P = 0.025), multiple concomitant nodules (OR, 8.700; 95% CI, 4.401- 17.197; P< 0.001), and abutting pleura (OR, 3.759; 95% CI, 1.407- 10.044; P = 0.008). The indicators for malignant PSNs were the following: lobulation (OR, 3.904; 95% CI, 1.956- 7.791; P< 0.001), spiculation (OR, 4.980; 95% CI, 2.202- 11.266, P< 0.001), and pleural indentation (OR, 4.514; 95% CI, 1.223- 16.666; P = 0.024).Conclusion: In patients younger than 55 years, PSNs with homogeneous density, ill-defined border, halo sign, multiple concomitant nodules, and abutting pleura should be highly suspected as absorbable ones.Keywords: solid nodule, absorbable nodule, follow-up, tomography, x-ray computed